Aplikasi Musik Instrumental Dalam Menurunkan Ansietas Pada Pasien Prioritas 4 di Ruang Unit Gawat Darurat - Tambi, Imelda Feneranda; Hurai, Rufina; Ismiati, Theresia Tutik (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIKes Panti Waluya Malang, 2023)
Background: The Emergency departments have a busy, noisy environment and can cause anxiety to patients. Patients who come to the emergency room have increased anxiety due to the unfamiliar environment, crowds, and actions that are carried out quickly. The increasing level of anxiety can have an effect on the pain experienced by the patient. Priority 4 patients usually suffer from an acute incident with a stable condition and often have a long waiting time. Management of anxiety and pain in patients is not only done by using medical and invasive therapy. Independent nursing interventions can also be carried out by nurses. Interventions to deal with anxiety in the emergency room are very important. The actions taken should be able to help the patient to adjust to the emergency room environment and the various actions taken. Purpose: To determine the effect of music therapy to reduce anxiety in priority 4 patients in the emergency department. Methods:This research method was quasi-experimental, the sampling technique used is purposive sampling. The population in this study was priority 4 patients in the Emergency Room. The instrument used to measure anxiety was the State Anxiety Scale. This study consisted of a control group and a treatment group of 45 respondents. Data analysis used the Wilcoxon test and used SPSS 23 software. Result:There is an influence of Instrumental Music Application in Reducing Anxiety in Priority 4 Patients in the Emergency Room with a significance value of 0.013 Conclusion: The Use of Instrumental Music Can Reduce Anxiety in Priority 4 Patients in the Emergency Room Music therapy can be given as a nurse's independent intervention to prioritize 4 patients in emergency departments. Music therapy canreduce the patient's anxiety level about noise and the actions taken in the emergency room Keywords: Anxiety, Emergency Departements, Music Intervention